2018
DOI: 10.1248/cpb.c17-00824
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Complex of Methyl-β-cyclodextrin with Adamantane-Grafted Hyaluronic Acid as a Novel Antitumor Agent

Abstract: Methyl-β-cyclodextrin (M-β-CyD) exhibits cytotoxic activity, and has the potentials as an antitumor agent. However, a tumor-selectivity of M-β-CyD is low, leading to low antitumor activity and the adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…In this study, we demonstrated that MβCD is a potential enhancer of the BITC-induced antiproliferation in human colorectal cancer cells. MβCD is accepted as an effective agent to remove the plasma membrane cholesterol [20] and reported to induce cholesterol efflux in HCT-116 cells [26], consistent with the present result Figure 1. The non-toxic concentration of MβCD (2.5 mM) enhanced the BITCinduced antiproliferation (Figure 2(b)) and apoptosis induction (Figure 3(b)) without change in the BITC accumulation (Figure 1(c)).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we demonstrated that MβCD is a potential enhancer of the BITC-induced antiproliferation in human colorectal cancer cells. MβCD is accepted as an effective agent to remove the plasma membrane cholesterol [20] and reported to induce cholesterol efflux in HCT-116 cells [26], consistent with the present result Figure 1. The non-toxic concentration of MβCD (2.5 mM) enhanced the BITCinduced antiproliferation (Figure 2(b)) and apoptosis induction (Figure 3(b)) without change in the BITC accumulation (Figure 1(c)).…”
Section: Discussionsupporting
confidence: 90%
“…Methyl-b-cyclodextrin (MbCD) has been mainly applied as a drug carrier in the pharmaceutical field (Loftsson and Duchene 2007) and as a cholesterol-depleting reagent in cell biological studies on lipid rafts (Ashrafzadeh and Parmryd 2015). It has also been reported that MbCD has potential antitumor efficacy and has the possibility of recruiting as an antitumor drug (Grosse et al 1998a;1998b;Gotoh et al 2014;Resni et al 2015;Elamin et al 2018). Recently, accumulating evidence supports that cyclodextrins also have an anti-atherosclerotic efficacy (Zimmer et al 2016;Ao et al 2016a;Pilely et al 2019;Wang et al 2019;Kim et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The smaller nanogels were taken up by two kinds of tumor cells (HeLa and HepG2) (Choi et al, ). Adamantane‐grafted hyaluronic acid can work as carrier for methyl‐β‐cyclodextrin through supramolecular assembly and proved to be a potential antitumor agent (Elamin, Yamashita, Higashi, Motoyama, & Arima, ).…”
Section: Polysaccharidesmentioning
confidence: 99%